Analysis of Traffic Congestion Impact Based on Road User Perception: A Case Jalan Gadjah Mada, Batam-Indonesia - Vivi Indiana Afilia; Jody Martin Ginting (LEADER: Civil Engineering and Architecture Journal, 2023)
Traffic congestion is a worldwide problem caused by population growth, heavy traffic due to the mixing of public, regional, and local transit traffic, and insufficient road capacity to accommodate the amount of transportation. This research aims to determine the impact of traffic congestion on road users' perception of Gadjah Mada Street (Pura Agung Amerta Bhuana - UIB) in Batam City. The methods used in this research are quantitative and qualitative. The data source used in this research is primary data. Primary data was obtained by distributing questionnaires to road users containing questions related to the impact of traffic congestion. Based on research that has been conducted, traffic congestion can have an effect on the economy, psychology, and productivity of road users.